Malaysia Environment and Atmosphere with Arab Tourist Loyalty and Satisfaction - Gadah Atiq, Alamer; Binti Mat Sharif, Zainon (International Journal of Engineering and Technology, 2018)
With the persistent development of tourism in Malaysia, tourist loyalty has become a vital topic in tourism studies. Researchers often examine this with little focus on the relations and interaction between tourist loyalty and the factors of tourism satisfaction. This study was conducted to examine the factors influencing Arab touristsâ€™ loyalty towards tourism in Malaysia. Questionnaires were delivered conveniently to 30 Arab tourists at Kuala Lumpur International Airport (KLIA). From the overall results of this study, it can be concluded that the regression model revealed that the independent variables entered into the regression model were significant predictors of tourist loyalty. The coefficient of destination (R2) showed that about 76.00% of variance in tourist loyalty was explained by the predictor variable.Â Â Â